Indonesia : Public Spending in a Time of Change - World Bank (Washington, DC, 2013)
The study identifies strategic priorities for restoring sound public finances, emphasizing the need to maintain fiscal sustainability, under a constrained budget, and the need to improve the processes for making budgetary allocations, and budget implementation, towards greater fiscal transparency. It reviews Indonesia's public spending during the crisis, and the unavoidable build-up of fiscal pressure, its indebtedness, and fiscal risks, coupled with policy implications. Improvements to the budget allocation process are examined, focusing on budgetary management processes, across levels of government, and on the impact of decentralization - which could possibly reinforce civil society participation. A shift in the fiscal policy focus, towards maintaining fiscal sustainability, and ensuring economic recovery is recommended. Nonetheless, risks may threaten fiscal sustainability, namely, macroeconomic fluctuations, contingent liabilities, and decentralization. To minimize risks, the study suggests a combination of domestic revenue generation efforts, spending cuts, accelerated privatization, aggressive asset recovery, and external finance.